Nursing attributions in cancer patient care through complementary therapies (Research, Society and Development, 2022)
Cancer is a generic term for a large group of diseases characterized by the growth of abnormal cells beyond their usual limits that can invade adjacent parts of the body and/or other organs. Other common terms used are malignant tumors and neoplasms. Cancer can affect almost any part of the body and has many anatomical and molecular subtypes that require specific management strategies. The objective of this study was to analyze the role of nursing in complementary therapies in cancer patients in scientific productions. This research is an integrative literature review with a quantitative approach to data. The Pubmed, Bireme and Cinahl databases were consulted using descriptors and keywords. The results showed that integrative therapies have great impacts on promoting a better quality of life and survival of cancer patients in palliative care when combined with other drug therapies that strengthen their physiological and immunological needs. In the care of patients undergoing treatment for benign or malignant neoplasms, the nursing professional is essential for understanding, psychological and emotional assistance, overcoming barriers and accepting multidisciplinary care and, consequently, improving the quality of life or reducing injuries and complications, thus, the nurse is an actor in this care environment, promoting the integration of technologies and complementary therapies for the patient's health, with a humanistic and holistic view of the client, promoting better living conditions for the patient to face their limitations.